COPD treatment case III: COPD with pre-diabetes - Kocks, Janwillem (Henry Stewart Talks, 2016)
GOLD guideline, Metabolic effects of COPD treatment, Case management, An updated version, which will include the latest GOLD COPD recommendations, will be released in November 2017